Progress of Learning Arabic Outcome for State Islamic University Students - Hilmi, Danial; Toifah, Nur; Sa’diyah, Halimatus (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3171, 2024)
The Arabic language learning process does not always have an impact on mastery of language skills. This is evident in the progress of Arabic language learning outcomes which absolutely have a good impact. In relation to this, this study aims to describe and compare the progress of Arabic language learning outcomes of students at PTKIN. The method used is through a descriptive quantitative approach with a population of all language center students and samples taken randomly from 264 students of UIN Maulana Malik Ibrahim Malang and 125 students of UIN Antasari Banjarmasin. Data collection techniques were obtained through questionnaire data mining by filling out a google form. Meanwhile, the results of the study showed that the average progress of UIN Malang students' learning outcomes was 73.31, and UIN Banjarmasin students were 76.63. This shows that the development of student learning outcomes is quite diverse and efforts need to be made to improve the learning process, especially for students in elementary classes.